First description of an in vitro culture system for Eimeria ovinoidalis macromeront formation in primary host endothelial cells. Issue 5 (October 2016) - Carrau, Tessa; Silva, Liliana Machado Ribeiro; Pérez, David; Ruiz de Ybáñez, Rocio; Taubert, Anja; Hermosilla, Carlos
Abstract: The apicomplexan parasite Eimeria ovinoidalis is distributed worldwide and causes clinical ovine coccidiosis. As one of the most pathogenic species in sheep, the principal clinical sign is profuse diarrhoea in young animals, which leads to important economic losses in the ovine industry. We here aimed to establish an in vitro culture system for the development of E. ovinoidalis macromeronts, as no suitable systems are currently available for any ovine Eimeria species. Faecal samples containing more than 90% of E. ovinoidalis oocysts were collected from naturally infected lambs and ewes in Murcia Region (Spain). E. ovinoidalis oocysts were collected, left to sporulate in potassium dichromate and stored at 4 °C until further studies were conducted. Moreover, a suitable excystation protocol was effectively established, resulting in the release of viable sporozoites, which were allowed to infect primary bovine umbilical vein endothelial cells (BUVEC) and permanent bovine colonic epithelial cells (BCEC) . In vitro first merogony was successfully accomplished exclusively in BUVEC leading to macromeront formation (up to 100 μm) and the release of fully developed and viable merozoites I stages. Given that we were able to establish a suitable in vitro system for the first merogony of such pathogenic Eimeria species in sheep, advances might be further made not only on studies regarding the control of ovine coccidiosis, such as drug screenings, but also on the better understanding of molecular parasite–host cell interactions as already demonstrated for other ruminant Eimeria species. Graphical abstract: Highlights: Establishment of a suitable E. ovinoidalis excystation protocol. In vitro first E. ovinoidalis merogony BUVEC leading to macromeront I formation. Development and viable merozoites I stages of E. ovinoidalis.